Maytenus guianensis klotzsch ex reissek (celastraceae): Ethnopharmacological aspects and isolated constituents - Lima, Renato Abreu; Meneguetti, Dionatas Ulises; Hurtado, Fernanda Bay; Militão, Júlio Linhares; Facundo, Valdir Alves (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2017)
This study consists of a literature review on the traditional use of the medicinal plant Maytenus guianensis, which was carried out using the databases: LILACS, SciELO, and PubMed. M. guianensis is popularly known as xixuá and occurs throughout the tropical and subtropical band of the world. In Brazil, its leaves, bark, and roots are used as tea or macerated for the treatment of inflammation and infections in general. It is also popularly used to treat rheumatism and worm infections. These medicinal uses which have experimental support seem to be mainly associated with the presence of triterpenes.